Análise fractal de microestruturas em pastas de cimento Portland : influência das condições de cura - Bespalhuk, Ketholyn Jaqueline (2021)
As cement is a material with cohesive properties, low cost, high versatility and good moldability, it is highly used in construction and renovation of structures, such as buildings, bridges and viaducts. However, both the conditions and the curing time intervene in the microstructural characteristics and properties of cementitious materials in their various constitutions. Over time and according to the type of cure, morphological changes in the microstructures of cementitious matrices occur as the hydration process occurs, influencing the mechanical properties and the durability of the material. Thus, to investigate the influence of the curing condition (ambient or submerged) on the morphology and compressive strength of the hardened pastes of 7 and 28 days, cylindrical specimens were produced. The fractured samples in the compressive strength test and the surface samples were analyzed by microscopy techniques. The results showed that over time the cementitious matrix becomes more filled by a solid structure resulting from the cement hydration process, influencing the mechanical properties of the structure. The quantifications of the morphological characteristics of the hydrated cement were correlated with the mechanical tests and showed that the local and global fractal dimension increase with time and that this increase is accompanied by the increase in the compressive strength, which may indicate that a greater difficulty in the propagation of the cracks, which generates a more broken fractal figure, may be associated with greater resistance to fracture.